Assessment of Resistance to Red rot (Colletotrichum falcatum Went) Disease by Different Methods of Inoculation in Sugarcane Germplasm - Bharathi, V.; Sudhakar, R. (International Journal of Bio-resource and Stress Management, 2012)
Sugarcane genotypes were screened for their resistance to red rot pathogen (Colletotrichum falcatum Went.) at the Sugarcane and Rice Research Station, Rudrur consecutively for three years i.e., from 2003-2006. Out of fifty five early and midlate genotypes, twenty six were found moderately resistant to red rot. Sixteen genotypes were found to be resistant and three were moderately susceptible. Four early and three midlate entries showed susceptible reaction while the 2000 R 551 was found highly susceptible to red rot pathogen.